Tele-health in theory versus practice: A comparative look at the United States and Singapore - Francis Pereira; Elizabeth Fife (International Telecommunications Society (ITS), 2021)
A global and growing shortage of medical doctors and nurses, exacerbated by increasing life expectancy, is generating greater cost pressures on health care around the world. Many industry analysts and health care professionals have argued that early detection and preventive care, as well as education, is a solution to the escalating costs of medical care. In this respect, telemedicine can help alleviate these pressures, as well as extend medical services to under-served or unserved areas.
Keywords: 330